Problemas na manutenção de sistemas legados: um estudo de caso - Costa, Fernanda Guimarães (Universidade do Vale do Rio dos Sinos, 2018)
The maintenance and evolution of systems present several challenges because they involve development in a legacy environment. Especially when these legacy systems have no documentation, no standardization, have an old technology, no testing or an experienced team. Due to these difficulties, a case study was developed in the legacy system of a company from Minas Gerais, aiming to improve the product developed and the maintenance process.The system studied is essential for the company and for the operation of other systems, and it is necessary to present a maintenance process that supports its evolution. The objective of the study was to propose improvements in the process of development of the teams involved in the maintenance and evolution of the system. The results presented are a solution of problems, adapted from good practices of the literature, for 5 priority problems in the legacy system, the perception of those involved.
Keywords: Ambiente legado; Manutenção; Desenvolvimento das equipes; Práticas da literatura; Literature practices; Maintenance; Team development; Práticas da literatura